2019
DOI: 10.1002/advs.201901822
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nanomatrix‐Induced Self‐Organization of Neural Stem Cells into Miniature Substantia Nigra‐Like Structures with Therapeutic Effects on Parkinsonian Rats

Abstract: Substantia nigra (SN) is a complex and critical region of the brain wherein Parkinson's disease (PD) arises from the degeneration of dopaminergic neurons. Miniature SN‐like structures (mini‐SNLSs) constructed from novel combination of nanomaterials and cell technologies exhibit promise as potentially curative cell therapies for PD. In this work, a rapid self‐organization of mini‐SNLS, with an organizational structure and neuronal identities similar to those of the SN in vivo, is achieved by differentiating neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
(57 reference statements)
1
9
0
Order By: Relevance
“… 95 Silica nanozigzags exhibit a unique groove-like topography, and their inherent physical characteristics, such as topographical features and stiffness, may play an important role in promoting specific neuronal phenotypic differentiation. 95 …”
Section: Combined Nanotherapeutic and Stem Cell Therapeutic Strategie...mentioning
confidence: 99%
“… 95 Silica nanozigzags exhibit a unique groove-like topography, and their inherent physical characteristics, such as topographical features and stiffness, may play an important role in promoting specific neuronal phenotypic differentiation. 95 …”
Section: Combined Nanotherapeutic and Stem Cell Therapeutic Strategie...mentioning
confidence: 99%
“…Based on this concept, Zhang et al . attempted to induce differentiation in stem cell analogs of brain tissue using the biological activity of nanomaterials [ 196 ]. Through glancing angle deposition, they developed silica-based organic sculptured extracellular nanomatrices (iSECnMs) that were carved into helices (nanohelices, NHs) and zigzags (nanozigzags, NZs) (Fig.…”
Section: Nano-biological Effects Of Nanomaterials Used For Pd Treatmentmentioning
confidence: 99%
“…Neural progenitor cells (NPCs) are self-renewing, multipotent cells that can be differentiated into neurons through safer, more direct, and more efficient processes than other kinds of stem cells . Recently, the transplantation of NPCs has been proposed as a promising therapeutic strategy for neurodegenerative diseases, including Alzheimer’s disease (AD) and Parkinson’s disease (PD), which are major public health concerns due to accelerated aging of the world. However, how to improve the survival rate and promote neuronal differentiation after the transplantation of NPCs under oxidative stress, the main pathological feature in the brain of AD and PD, is still a major challenge for NPC therapy . A growing body of literature has shown that the balance of intracellular redox homeostasis plays a vital role in regulating the survival, renewal, and differentiation NPCs. Reactive oxygen species (ROS), essential for the maintenance of intracellular redox homeostasis at physiological levels, is an important mediator in the biological process of NPCs .…”
Section: Introductionmentioning
confidence: 99%